The Influence of Global Environmental Change on Infectious Disease Dynamics: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
The twentieth century witnessed an era of unprecedented, large-scale, anthropogenic changes to the natural environment. Understanding how environmental factors directly and indirectly affect the emergence and spread of infectious disease has assumed global importance for life on this planet. While the causal links between environmental change and disease emergence are complex, progress in understanding these links, as well as how their impacts may vary across space and time, will require transdisciplinary, transnational, collaborative research. This research may draw upon the expertise, tools, and approaches from a variety of disciplines. Such research may inform improvements in global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health. The Influence of Global Environmental Change on Infectious Disease Dynamics is the summary of a workshop hosted by the Institute of Medicine Forum on Microbial Threats in September 2013 to explore the scientific and policy implications of the impacts of global environmental change on infectious disease emergence, establishment, and spread. This report examines the observed and potential influence of environmental factors, acting both individually and in synergy, on infectious disease dynamics. The report considers a range of approaches to improve global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health in the face of ongoing global environmental change.
Keywords: Health and Medicine; Conflict and Security Issues

The Use and Effectiveness of Powered Air Purifying Respirators in Health Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Protecting 18 million United States health care workers from infectious agents - known and unknown - involves a range of occupational safety and health measures that include identifying and using appropriate protective equipment. The 2009 H1N1 influenza pandemic and the 2014 Ebola virus outbreak in West Africa have called raised questions about how best to ensure appropriate and effective use of different kinds of personal protective equipment such as respirators, not only to promote occupational safety but also to reduce disease transmission. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care is the summary of a workshop convened by the Institute of Medicine Standing Committee on Personal Protective Equipment for Workplace Safety and Health to explore the current state of practices and research related to powered air purifying respirator (PAPRs) and potential updates to performance requirements. Presentations and discussions highlighted current health care practices using PAPRs and outlined the research to date on the use and effectiveness of PAPRs in health care settings with a focus on the performance requirements. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care focuses on efficacy, current training, maintenance, supplies, and possible enhancements and barriers to use in inpatient, clinic, nursing home, and community (home) settings. This report also explores the strengths and weaknesses of using various approaches to health care PAPR standards.
Keywords: Health and Medicine

Preparing for an Influenza Pandemic: Personal Protective Equipment for Healthcare Workers - Institute of Medicine (The National Academies Press, 2008)
During an influenza pandemic, healthcare workers will be on the front lines delivering care to patients and preventing further spread of the disease. As the nation prepares for pandemic influenza, multiple avenues for protecting the health of the public are being carefully considered, ranging from rapid development of appropriate vaccines to quarantine plans should the need arise for their implementation. One vital aspect of pandemic influenza planning is the use of personal protective equipment (PPE)—the respirators, gowns, gloves, face shields, eye protection, and other equipment that will be used by healthcare workers and others in their day-to-day patient care responsibilities. However, efforts to appropriately protect healthcare workers from illness or from infecting their families and their patients are greatly hindered by the paucity of data on the transmission of influenza and the challenges associated with training and equipping healthcare workers with effective personal protective equipment. Due to this lack of knowledge on influenza transmission, it is not possible at the present time to definitively inform healthcare workers about what PPE is critical and what level of protection this equipment will provide in a pandemic. The outbreaks of severe acute respiratory syndrome (SARS) in 2003 have underscored the importance of protecting healthcare workers from infectious agents. The surge capacity that will be required to reduce mortality from a pandemic cannot be met if healthcare workers are themselves ill or are absent due to concerns about PPE efficacy. The IOM committee determined that there is an urgent need to address the lack of preparedness regarding effective PPE for use in an influenza pandemic. Preparing for an Influenza Pandemic : Personal Protective Equipment for Healthcare Workers identifies that require expeditious research and policy action: (1) Influenza transmission research should become an immediate and short-term research priority so that effective prevention and control strategies can be developed and refined. The current paucity of knowledge significantly hinders prevention efforts. (2) Employer and employee commitment to worker safety and appropriate use of PPE should be strengthened. Healthcare facilities should establish and promote a culture of safety. (3) An integrated effort is needed to understand the PPE requirements of the worker and to develop and utilize innovative materials and technologies to create the next generation of PPE capable of meeting these needs.
Keywords: Health and Medicine

Emerging Viral Diseases: The One Health Connection: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In the past half century, deadly disease outbreaks caused by novel viruses of animal origin - Nipah virus in Malaysia, Hendra virus in Australia, Hantavirus in the United States, Ebola virus in Africa, along with HIV (human immunodeficiency virus), several influenza subtypes, and the SARS (sudden acute respiratory syndrome) and MERS (Middle East respiratory syndrome) coronaviruses - have underscored the urgency of understanding factors influencing viral disease emergence and spread. Emerging Viral Diseases is the summary of a public workshop hosted in March 2014 to examine factors driving the appearance, establishment, and spread of emerging, re-emerging and novel viral diseases; the global health and economic impacts of recently emerging and novel viral diseases in humans; and the scientific and policy approaches to improving domestic and international capacity to detect and respond to global outbreaks of infectious disease. This report is a record of the presentations and discussion of the event.
Keywords: Health and Medicine

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency – both within the U.S. government and across the global health field.
Keywords: Health and Medicine

Research Priorities to Inform Public Health and Medical Practice for Ebola Virus Disease: Workshop in Brief - Institute of Medicine; National Research Council (The National Academies Press, 2014)
The 2014 epidemic of Ebola Virus Disease (EVD), caused by a filovirus, has affected multiple countries in West Africa (Guinea, Liberia, Sierra Leone, Nigeria, and Senegal), along with Spain and the United States, becoming the worst EVD outbreak since its discovery in 1976. Until 2014, previous outbreaks have been confined to smaller geographic areas and often only affected a few hundred people. Confirmed and suspected cases of EVD have now occurred in the United States through human-to-human transmission, requiring the U.S. medical and public health systems to prepare for and respond to domestic cases of EVD. The heightened awareness and attention to the disease in the United States has also led to questions from affected communities on specific characteristics of the virus, how the virus behaves, and personal protective equipment and personal protective behaviors that can be used to prevent its spread and reduce exposure. At the request of the Office of the Assistant Secretary for Preparedness and Response, the National Institutes of Health, and the Centers for Disease Control and Prevention, the Institute of Medicine , in collaboration with the National Research Council, convened a workshop on November 3, 2014, with key stakeholders and experts to discuss the research priorities that could guide medical and public health practice. Discussions included the degree of transmission and biopersistence of the virus under a range of conditions and on a variety of materials, as well as issues of handling potentially infected materials, decontamination, and the training and personal protective equipment usage of traditional and nontraditional workers involved in the full spectrum of this response. Research Priorities to Inform Public Health and Medical Practice for Ebola Virus Disease summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Enabling Rapid and Sustainable Public Health Research During Disasters: Summary of a Joint Workshop by the Institute of Medicine and the U.S. Department of Health and Human Services - Institute of Medicine (The National Academies Press, 2015)
Over the past decade, preparedness and response capacities of government agencies, hospitals and clinics, public health agencies, and academic researchers in the United States and abroad have been challenged by a succession of public health emergencies, ranging from radiological threats to pandemics to earthquakes. Through After Action Reports, each of these emergencies has yielded important information and lessons learned that can inform future disaster response and recovery efforts. However, important information that needs to be collected during and immediately following these emergencies is often missed because of barriers and obstacles to gathering such data, such as varying institutional review board restrictions in different states, no sustainable funding network for this type of work, uncertainty on who should be involved in research response, and a lack of knowledge around how best to integrate research into response and recovery frameworks. Taking action to enable medical and public health research during disasters was the focus of a workshop held on June 12 and 13, 2014, coordinated and supported jointly by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events, National Institute of Environmental Health Sciences, the National Library of Medicine, the U.S. Department of Health and Human Services' Office of the Assistant Secretary for Preparedness and Response, and the Centers for Disease Control and Prevention. Invited speakers and participants from federal, state, and local government, academia, and community and worker organizations came together to discuss how to integrate research into existing response structures; identify critical research needs and priorities; identify obstacles and barriers to research; discuss structures and strategies needed for deployment of a research study; share ideas, innovations, and technologies to support research; and explore data collection tools and data-sharing mechanisms for both rapid and longitudinal research. Enabling Rapid and Sustainable Public Health Research During Disasters summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Engaging the Private-Sector Health Care System in Building Capacity to Respond to Threats to the Public's Health and National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Disasters tend to cross political, jurisdictional, functional, and geographic boundaries. As a result, disasters often require responses from multiple levels of government and multiple organizations in the public and private sectors. This means that public and private organizations that normally operate independently must work together to mount an effective disaster response. To identify and understand approaches to aligning health care system incentives with the American public’s need for a health care system that is prepared to manage acutely ill and injured patients during a disaster, public health emergency, or other mass casualty event, the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop on March 20 and 21, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Perspectives on Research with H5N1 Avian Influenza: Scientific Inquiry, Communication, Controversy: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2013)
When, in late 2011, it became public knowledge that two research groups had submitted for publication manuscripts that reported on their work on mammalian transmissibility of a lethal H5N1 avian influenza strain, the information caused an international debate about the appropriateness and communication of the researchers' work, the risks associated with the work, partial or complete censorship of scientific publications, and dual-use research of concern in general. Recognizing that the H5N1 research is only the most recent scientific activity subject to widespread attention due to safety and security concerns, on May 1, 2012, the National Research Council's Committee on Science, Technology and Law, in conjunction with the Board on Life Sciences and the Institute of Medicine's Forum on Microbial Threats, convened a one-day public workshop for the purposes of 1) discussing the H5N1 controversy; 2) considering responses by the National Institute of Allergy and Infectious Diseases (NIAID), which had funded this research, the World Health Organization, the U.S. National Science Advisory Board for Biosecurity (NSABB), scientific publishers, and members of the international research community; and 3) providing a forum wherein the concerns and interests of the broader community of stakeholders, including policy makers, biosafety and biosecurity experts, non-governmental organizations, international organizations, and the general public might be articulated. Perspectives on Research with H5N1 Avian Influenza: Scientific Enquiry, Communication, Controversy summarizes the proceedings of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Vector-Borne Diseases: Understanding the Environmental, Human Health, and Ecological Connections: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Vector-borne infectious diseases, such as malaria, dengue fever, yellow fever, and plague, cause a significant fraction of the global infectious disease burden; indeed, nearly half of the world's population is infected with at least one type of vector-borne pathogen (CIESIN, 2007; WHO, 2004a). Vector-borne plant and animal diseases, including several newly recognized pathogens, reduce agricultural productivity and disrupt ecosystems throughout the world. These diseases profoundly restrict socioeconomic status and development in countries with the highest rates of infection, many of which are located in the tropics and subtropics. Although this workshop summary provides an account of the individual presentations, it also reflects an important aspect of the Forum philosophy. The workshop functions as a dialogue among representatives from different sectors and allows them to present their beliefs about which areas may merit further attention. These proceedings summarize only the statements of participants in the workshop and are not intended to be an exhaustive exploration of the subject matter or a representation of consensus evaluation. Vector-Borne Diseases : Understanding the Environmental, Human Health, and Ecological Connections, Workshop Summary (Forum on Microbial Threats) summarizes this workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases – including malaria, dengue, yellow fever, and plague – together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans. Domestic and international capabilities to detect, identify, and effectively respond to vector-borne diseases are limited. Few vaccines have been developed against vector-borne pathogens. At the same time, drug resistance has developed in vector-borne pathogens while their vectors are increasingly resistant to insecticide controls. Furthermore, the ranks of scientists trained to conduct research in key fields including medical entomology, vector ecology, and tropical medicine have dwindled, threatening prospects for addressing vector-borne diseases now and in the future. In June 2007, as these circumstances became alarmingly apparent, the Forum on Microbial Threats hosted a workshop to explore the dynamic relationships among host, pathogen(s), vector(s), and ecosystems that characterize vector-borne diseases. Revisiting this topic in September 2014, the Forum organized a workshop to examine trends and patterns in the incidence and prevalence of vector-borne diseases in an increasingly interconnected and ecologically disturbed world, as well as recent developments to meet these dynamic threats. Participants examined the emergence and global movement of vector-borne diseases, research priorities for understanding their biology and ecology, and global preparedness for and progress toward their prevention, control, and mitigation. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Infectious Disease Movement in a Borderless World: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Modern transportation allows people, animals, and plants--and the pathogens they carry--to travel more easily than ever before. The ease and speed of travel, tourism, and international trade connect once-remote areas with one another, eliminating many of the geographic and cultural barriers that once limited the spread of disease. Because of our global interconnectedness through transportation, tourism and trade, infectious diseases emerge more frequently; spread greater distances; pass more easily between humans and animals; and evolve into new and more virulent strains. The IOM's Forum on Microbial Threats hosted the workshop "Globalization, Movement of Pathogens (and Their Hosts) and the Revised International Health Regulations" December 16-17, 2008 in order to explore issues related to infectious disease spread in a "borderless" world. Participants discussed the global emergence, establishment, and surveillance of infectious diseases; the complex relationship between travel, trade, tourism, and the spread of infectious diseases; national and international policies for mitigating disease movement locally and globally; and obstacles and opportunities for detecting and containing these potentially wide-reaching and devastating diseases. This document summarizes the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Gain-of-Function Research: Summary of the Second Symposium, March 10-11, 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 10-11, 2016, the National Academies of Sciences, Engineering, and Medicine held a public symposium on potential U.S. government policies for the oversight of gain-of- function (GOF) research. This was the Academies' second meeting held at the request of the U.S. government to provide a mechanism to engage the life sciences community and the broader public and solicit feedback on optimal approaches to ensure effective federal oversight of GOF research as part of a broader U.S. government deliberative process. The first symposium, held in December 2014, examined the underlying scientific and technical questions surrounding the potential risks and benefits of GOF research involving pathogens with pandemic potential. The second symposium focused on discussion of the draft recommendations regarding GOF research of a Working Group of the National Science Advisory Board for Biosecurity. This report summarizes the key issues and ideas identified during the second symposium.
Keywords: Health and Medicine

Building Communication Capacity to Counter Infectious Disease Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Building communication capacity is a critical piece of preparing for, detecting, and responding to infectious disease threats. The International Health Regulations (IHR) establish risk communication—the real-time exchange of information, advice, and opinions between experts or officials and people who face a threat to their survival, health, and economic or social well-being—as a core capacity that World Health Organization member states must fulfill to strengthen the fight against these threats. Despite global recognition of the importance of complying with IHR, 67 percent of signatory countries report themselves as not compliant. By investing in communication capacity, public health and government officials and civil society organizations facing health crises would be prepared to provide advice, information, and reassurance to the public as well as to rapidly develop messages and community engagement activities that are coordinated and take into account social and behavioral dynamics among all sectors. To learn about current national and international efforts to develop the capacity to communicate effectively during times of infectious disease outbreaks, and to explore gaps in the research agenda that may help address communication needs to advance the field, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine convened a 1.5 day workshop on December 13 and 14, 2016, in Washington, DC. Participants reviewed progress and needs in strengthening communication capacity for dealing with infectious disease threats for both outbreaks and routine challenges in the United States and abroad. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Global Health Risk Framework: Governance for Global Health: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Governance for Global Health Workshop are summarized in this report.
Keywords: Health and Medicine

The Impact of Globalization on Infectious Disease Emergence and Control: Exploring the Consequences and Opportunities: Workshop Summary - Institute of Medicine (The National Academies Press, 2006)
Globalization is by no means a new phenomenon; transcontinental trade and the movement of people date back at least 2,000 years, to the era of the ancient Silk Road trade route. The global spread of infectious disease has followed a parallel course. Indeed, the emergence and spread of infectious disease are, in a sense, the epitome of globalization. Although some experts mark the fall of the Berlin Wall as the beginning of this new era of globalization, others argue that it is not so new. The future of globalization is still in the making. Despite the successful attempts of the developed world during the course of the last century to control many infectious diseases and even to eradicate some deadly afflictions, 13 million people worldwide still die from such diseases every year. On April 16 and 17, 2002, the Forum on Emerging Infections held a working group discussion on the influence of globalization on the emergence and control of infectious diseases. The contents of the unattributed sections are based on the presentations and discussions that took place during the workshop. The Impact of Globalization on Infectious Disease Emergence and Control report summarizes the presentations and discussions related to the increasing cross-border and cross-continental movements of people and how this could exacerbate the emergence and global spread of infectious diseases. This report also summarizes the means by which sovereign states and nations must adopt a global public health mind-set and develop a new organizational framework to maximize the opportunities and overcome the challenges created by globalization and build the necessary capacity to respond effectively to emerging infectious disease threats.
Keywords: Health and Medicine

What You Need to Know About Infectious Disease - Institute of Medicine (The National Academies Press, 2011)
About a quarter of deaths worldwide--many of them children--are caused by infectious organisms. The World Health Organization reports that new infectious diseases are continuing to emerge and familiar ones are appearing in new locations around the globe. What's behind this trend? How can invisible organisms cause such harm? And to what extent has human behavior amplified the problem? What You Need to Know About Infectious Disease provides an overview of infectious disease, drawing on reports of the Institute of Medicine. Written for a general audience, it describes the biology, history, and future trends of some of the world's most widespread and harmful infections and explains what we need to do--as individuals and as a society--to address this global challenge.
Keywords: Health and Medicine

Understanding the Economics of Microbial Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Microbial threats, including endemic and emerging infectious diseases and antimicrobial resistance, can cause not only substantial health consequences but also enormous disruption to economic activity worldwide. While scientific advances have undoubtedly strengthened our ability to respond to and mitigate the mortality of infectious disease threats, events over the past two decades have illustrated our continued vulnerability to economic consequences from these threats. To assess the current understanding of the interaction of infectious disease threats with economic activity and suggest potential new areas of research, the National Academies of Sciences, Engineering, and Medicine planned a 1.5-day public workshop on understanding the economics of microbial threats. This workshop built on prior work of the Forum on Microbial Threats and aimed to help transform current knowledge into immediate action. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.
Keywords: Health and Medicine